Implementation of the Iqro Method in Overcoming Difficulties in Learning to Read the Qur'an for Students - Lilik Maulidiyah; Khaeruddin Yusuf; Irawan Hadi Patangu (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines the implementation of the Iqro' method to improve the Qur'an reading skills of fourth-grade students at an Integrated Islamic Elementary School. The study was motivated by low Qur'an literacy among students, particularly in recognizing hijaiyah letters, mastering harakat, and applying basic tajwid rules. The objectives of this research were to describe the initial reading ability, analyze the factors causing difficulties, evaluate the effectiveness of the Iqro' method, and identify supporting and inhibiting factors. This study employed a descriptive qualitative approach with data collected through participatory observation, semi-structured interviews, and documentation, involving 28 students, 3 teachers, 1 principal, and 5 parents. The findings indicate that the gradual implementation of the Iqro' method through sorogan and talaqi significantly improved students' Qur'an literacy, with an increase of 48–50%. The study emphasizes that individualized learning, parental involvement, and teacher guidance are crucial for effective Qur'an reading instruction. The contribution of this study is providing empirical evidence on the effectiveness of the Iqro' method in the context of Islamic elementary schools and highlighting practical strategies for teachers and parents. The results suggest that strengthening the Iqro' method positively impacts Qur'an literacy, serving as an essential reference for developing more effective Qur'an education practices.